2020
DOI: 10.1182/bloodadvances.2020002242
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of rivaroxaban compared with low-molecular-weight heparin in cancer-associated thromboembolism

Abstract: Guidelines provide differing recommendations regarding direct-acting oral anticoagulants vs low-molecular-weight heparin (LMWH) for treatment of cancer-associated thrombosis (CAT). This study was undertaken to evaluate the effectiveness and safety of rivaroxaban vs LMWH for treatment of CAT. Using US Surveillance, Epidemiology and End Results-Medicare–linked data from 2013 through 2016, we evaluated adults with active breast, lung, ovarian, or pancreatic cancer, who were admitted to the hospital or treated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Unexpectedly, the mortality was signi cantly higher in LMWH group compared to rivaroxaban group. The trend of all-cause mortality in the present study was similar to an Asian-based retrospective study and two prospective trials, but the other trials with cancer-associated VTE did not show distinct comparisons among vitamin K antagonist, LMWH and DOACs [30][31][32][33][34]. Indeed, LMWH group had high proportion of central PE, intermediate-risk PE, CCI score ≥ 3, and receiving palliative oncotherapy during the study period, which suggested that the more advanced cancer stage and heavier thrombotic burden might contributed to the increased risks of VTE recurrence and mortality.…”
Section: Discussionsupporting
confidence: 83%
“…Unexpectedly, the mortality was signi cantly higher in LMWH group compared to rivaroxaban group. The trend of all-cause mortality in the present study was similar to an Asian-based retrospective study and two prospective trials, but the other trials with cancer-associated VTE did not show distinct comparisons among vitamin K antagonist, LMWH and DOACs [30][31][32][33][34]. Indeed, LMWH group had high proportion of central PE, intermediate-risk PE, CCI score ≥ 3, and receiving palliative oncotherapy during the study period, which suggested that the more advanced cancer stage and heavier thrombotic burden might contributed to the increased risks of VTE recurrence and mortality.…”
Section: Discussionsupporting
confidence: 83%
“…A potential reason for the excess bleeding risk observed by Giustozzi et al includes their practice of bridging with low molecular weight heparin after the procedure rather than continuing anticoagulation without interruption, as is the usual practice at the institutions included in our study. Furthermore, more than half the patients included in the study by Giustozzi et al had a history of gastrointestinal and genitourinary malignancies that are more prone to bleeding with anticoagulation than other cancers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…includes their practice of bridging with low molecular weight heparin after the procedure rather than continuing anticoagulation without interruption, as is the usual practice at the institutions included in our study. Furthermore, more than half the patients included in the study by Giustozzi et al had a history of gastrointestinal and genitourinary malignancies that are more prone to bleeding with anticoagulation than other cancers 23 .…”
Section: Discussionmentioning
confidence: 99%